The Geopolitics Role of Energy in the National Security of Countries - Sayed Jalal Ahmadi (Integrated Journal for Research in Arts and Humanities, 2022)
Today, energy plays a role in the politics and economics of countries as one of the levers of power, and many of the current global politics and conflicts are affected by this. The dependence of industrialized and developing countries on such resources has given rise to new strategies in the field of energy security, because the political fate, economic potential and national interests of energy exporters and importers are tied to energy topic. Therefore, providing, maintaining and safeguarding the security of such a strategic commodity is a priority for the national interests of the producing and importing countries and also affects their national security. Currently, one of the most important geopolitical variables affecting the fate of countries is the energy variable and one of the ways that countries can increase their national security factor is to pay attention to the geopolitics of energy in the national and transnational contexts. The research method used in this study is descriptive-analytical and the data collection tool is library studies. Security and energy are now the focus of countries today and they seek to strengthen their power in both areas and to obviate security weaknesses and required energies and there is a significant relationship between energy and security.